Return Saham Melalui Likuiditas, Profitabilitas, Dan Solvabilitas - Rindy Citra Dewi; Yamasitha Yamasitha; Agam Mei Yudha; Reza Putri Ayuni (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2022)
This study aims to determine how much influence Liquidity, Profitability, and Solvency on Stock Return. This research was conducted on Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method of determining the sample in this study uses purposive sampling method so that from 193 populations, 44 companies can be obtained as samples. The data in this study were analyzed using multiple linear regression analysis techniques. The results of the study conclude that: (1) Liquidity has a significant effect on Stock Returns, (2) Profitability has no significant effect on Stock Returns, (3) Solvency has a significant effect on Stock Returns